Preparation of Ni-P-diamond coatings with dry friction characteristics and abrasive wear resistance. (January 2018) - Wang, Jian; Zhang, Feng-Lin; Zhang, Teng; Liu, Wen-Guang; Li, Wei-Xiong; Zhou, Yu-Mei
Abstract: The Ni-P-diamond composite coatings that contained diamond particles with various sizes in microns have been prepared by electroless plating. The effects of diamond particle size and heat-treatment on the microstructure, mechanical properties, dry friction behavior and abrasive wear performance of the Ni-P diamond composite coatings were investigated. It was discovered that a Ni-P diamond composite coating with the thickness of 30 μm could be obtained. The diamond particles (2–9 μm) could be homogeneously dispersed in the coatings with the volume fractions of 21%–25%. Subsequently to 400 °C for 2 h of heat treatment, the hardness of the Ni-P diamond coatings increased to approximately 1200 HV. The friction coefficients of the Ni-P diamond composite coatings were stable in the range of 0.4–0.52, whereas the Ni-P coating coefficient increased with time and finally reached to beyond 0.50. The addition of diamond particles could improve the wear resistance significantly, whereas as the diamond particle sizes increased, the friction wear resistance and the abrasive wear resistance increased. Graphical abstract: The hard quartz sand could easily penetrate and cut deeply into the soft Ni-P coating, causing a severe abrasive wear and higher weight loss. For the composites containing high-sized particles, these particles quite effectively resisted penetration and cut into the surface, whereas were not easily cut out by the slider due to the corresponding high size, high values of hardness and good bonding with the matrix. Highlights: Ni-P-diamond composite coatings contained diamond particles with various sizes are prepared. Hardness of Ni-P-diamond coatings is increased with the increasing of diamond particle size. Friction coefficient of Ni-P-diamond coatings are in the range of 0.40 0.52. Abrasive wear resistance of Ni-P diamond coatings are increased with rise of diamond particle size.